Recent and current low food intake – prevalence and associated factors in hospital patients from different medical specialities - Böhne, Sarah Elisabeth Jasmin; Hiesmayr, Michael; Sulz, Isabella; Tarantino, Silvia; Wirth, Rainer; Volkert, Dorothee (European Journal of Clinical Nutrition, 2022)
Background/Objectives: Poor food intake is a major etiological factor of malnutrition. This research aims to describe the prevalence of recent and current low food intake (LIRC) and to identify factors associated with LIRC in adult hospital patients from different medical specialities. Subject/Methods: 1865 patients participating in the nutritionDay survey 2016–2020 in Germany were included. LIRC was defined by decreased eating both on nutritionDay and in the week before hospitalisation. Multivariate binary logistic regression was used to identify factors associated with LIRC overall and in different specialities. Results: LIRC was observed in 21.1% of all patients, with the highest prevalence in Gastroenterology (26.6%) and the lowest in Neurology (11.2%). Weight loss within three months before nutritionDay (OR 2.62 [95% CI 1.93–3.56]), (very) poor self-rated health (2.17 [1.62–2.91]), female sex (1.98 [1.50–2.61]), uncertain weight loss (1.90 [1.03–3.51]), digestive disease (1.90 [1.40–2.56]), inability to walk without assistance (1.55 [1.14–2.12]) and emergency admission (1.38 [1.02–1.86]) were associated with increased risk, cardiac insufficiency (0.55 [0.37–0.83]) and being in a neurological ward (0.51 [0.28–0.92]) with decreased risk in the total sample. In Gastroenterology and Oncology, estimates were higher than in the entire sample; no significant associations were found in Neurology and Geriatrics, presumably due to the low prevalence of LIRC in Neurology and limited data quality in Geriatrics. Conclusion: LIRC is common in German hospital patients and associated with female sex, poor health and decreased functional status. Interdisciplinary differences suggest a discipline-specific approach to dealing with malnutrition.
CRIS-Team Scopus Importer:2022-04-22